The Effect of Early Breastfeeding Initiation (IMD) on Uterine Involution in Post Partum Mothers at Ninda Harni Clinic - Tambunan, Lili Yuliana; Umamy, Farida; Fitria, Aida (PT Inovasi Pratama Internasional, 2023)
The early initiation of breastfeeding is one of the factors affecting uterine involution. This is due to the stimulation and release of hormones, including oxytocin, which functions to stimulate the contraction of breast smooth muscles and also causes the contraction and retraction of uterine muscles. This will result in the compression of the blood vessels, thereby reducing the blood supply to the uterus. The objective of this study is to ascertain the relationship between early breastfeeding initiation and uterine involution in postpartum mothers. The study was conducted at Ninda Clinic on 26 postpartum mothers, of whom 13 had undergone IMD and 13 had not undergone IMD. The data were analyzed using the chi-square test. The results of this study demonstrated that 12 respondents (46.2%) exhibited normal TFU, while 14 respondents (53.8%) demonstrated abnormal TFU. It can be concluded that there is a relationship between early breastfeeding initiation (IMD) and involution in postpartum mothers, with a value of p=0.018 (0.018 <0.05). It is recommended that health workers, particularly midwives, provide health education about IMD in the postpartum period.